High-Performance Computing of 3D Magma Dynamics, and Comparison With 2D Simulation Results - Garg, Deepak; Papale, Paolo (Frontiers in Earth Science, 2022)
The dynamics of magma is often studied through 2D numerical simulations because 3D simulations are usually complex and computationally expansive. However, magmatic systems and physical processes are 3D and approximating them in 2D requires an evaluation of the information which is lost under different conditions. This work presents a physical and numerical model for 3D magma dynamics. The model is applied to study the dynamics of magma convection and mixing between andesitic and dacitic magmas. The 3D simulation results are compared with corresponding 2D simulations. We also provide details on the numerical scheme and its parallel implementation in C++ for high-performance computing. The performance of the numerical code is evaluated through strong scaling exercises involving up to >12000 cores.